Digital Identity and Distributed Ledger Technology: Paving the Way to a Neo-Feudal Brave New World? - Gstrein, Oskar J.; Kochenov, Dimitry (Frontiers in Blockchain, 2020)
While the digital layer of social interaction continues to evolve, the recently proclaimed hopes in the development of digital identity could be both naïf and dangerous. Rather than just asking ourselves how we could digitize existing features of identity management, and corresponding financial transactions on a community or state level, we submit that truly useful and innovative digital identities need to be accompanied by some significant rethinking of the essential basics behind the organization of the world. Once digital technologies leave the realm of purely on-line or deeply local projects, the confrontation with the world of citizenship’s biases and the random distribution of rights and duties precisely on the presumption of the lack of any choice and absolute pre-emption of any disagreement comes into a direct conflict with all the benefits Distributed Ledger Technology purports to enable. Some proponents of Distributed Ledger Technology-based identity systems envisage ‘cloud communities’ with truly ‘self-sovereign’ individuals picking and choosing which communities they belong to. We rather see a clear risk that when implemented at the global scale, digital identity systems could be deeply harmful, reinforcing and amplifying the most repugnant aspects of contemporary citizenship. In this contribution we present a categorization of existing digital identity systems from a governance perspective, and discuss it on basis of three corresponding case studies which allow us to infer opportunities and limitations of Distributed Ledger Technology based identity. Subsequently, we put our findings in the context of existing preconditions of citizenship law, and conclude with a suggestion of a combination of several tests which we propose to avoid the plunge into a neo-feudal ‘brave new world’. We would like to draw attention to the perspective that applying digital identity without rethinking the totalitarian assumptions behind the citizenship status will result in perfecting the current inequitable system, which is a move away from striving towards justice and a more dignified future of humanity. We see the danger that those might be provided with plenty of opportunities who already do not lack such under current governance structures, while less privileged individuals will witness their already weak position becoming increasingly worse.